The Influence of Technology and Human Resource Competence on Work Productivity at PT. TMMIN - Partimah, Partimah; Hidayat, Arif; Arifin, Rifqi Meinaufalni (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
This research is motivated by the phenomenon of productivity efficiency in the department of Welding Body Production Plant 1 PT TMMIN Karawang in 2023 which decreased to 98.79 (from the target of 99.6%). If calculated by annual production, an average of 65 units of cars per month must be outlined, from a total production of 5723 units (period of 2023). The purpose of this study is to determine how much influence technology and HR competencies on work productivity. This type of research quantitative, with data analysis techniques using Microsoft Excel and SPSS 20. The data collection technique is conducting field observations, distributing questionnaires, and documentation. The population in this study is the department of Welding Body Production Plant 1 PT TMMIN which was sampled using multistage cluster sampling technique, totaling 95 respondents. Research results the correlation coefficient of the technology variable (X1) has an R value of 0.434 which means a positive relationship with a moderate interpretation of work productivity. And the coefficient correlation of the HR competency variable (X2) has an R value of 0.306 which means positive relationship with low interpretation of work productivity. And simultaneously, the R2 value is 0.191 which means that technology and HR competencies have a significant effect on work productivity by 19,1%. It can be concluded, the better between technology and competence of human resources, the more work productivity will increase.